Neighborhood Conditions and Psychosocial Outcomes Among Middle-Aged African Americans - Maya Tabet; Erin A. Sanders; Mario Schootman; Jen Jen Chang; Fredric D. Wolinsky; Theodore K. Malmstrom; Douglas K. Miller (SAGE Publishing, 2017)
Objective: We examined associations between observed neighborhood conditions (good/adverse) and psychosocial outcomes (stress, depressive symptoms, resilience, and sense of control) among middle-aged and older African Americans. Methods: The sample included 455 middle-aged and older African Americans examined in Wave 10 of the African American Health (AAH) study. Linear regression was adjusted for attrition, self-selection into neighborhoods, and potential confounders, and stratified by the duration at current address (<5 vs ≥5 years) because of its hypothesized role as an effect modifier. Results: Among individuals who lived at their current address for ≥5 years, residing in neighborhoods with adverse versus good conditions was associated with significantly less stress (standardized β = −0.18; P = .002) and depressive symptoms (standardized β = −0.12; P = .048). Among those who lived at their current address for <5 years, residing in neighborhoods with adverse versus good conditions was not significantly associated with stress (standardized β = 0.18; P = .305) or depressive symptoms (standardized β = 0.36; P = .080). Conclusion: Neighborhood conditions appear to have significant, complex associations with psychosocial factors among middle-aged and older African Americans. This holds important policy implications, especially since adverse neighborhood conditions may still result in adverse physical health outcomes in individuals with >5 years at current residence despite being associated with better psychosocial outcomes.